Battered Women Syndrome: Need for Judicial Objectivity - Shrestha, Dibya; Bhandari, Nisha (Kathmandu School of Law Review, 2018)
When the victims of wife-beating are subjected to excessive violence, a syndrome occurs, which during a criminal procedure can be pleaded as BWS (Battered Women Syndrome). It is also referred to as Battered Spouse Syndrome. However; the condition is most common among women than that of men. Wife battering is the most common and least reported crimes in all types of society. Some never mention about it and bear the violence while some others seek help from the law. But there also exists a different group of battered women who kill their abusive partner without any remorse. Some scholars have claimed that is a normal reaction from a woman who has been subjected to acute battering and that they should be given defense by law while some others have opposed to this notion of Battered Woman Syndrome. BWS, as a very new concept to the legal and judicial system of Nepal, still has a lot of gaps to be filled. This paper will analyze the concept and practical implications of Battered Woman Syndrome alongside the legal and judicial trend in case of Nepal. Further, this paper will establish why Battered Women Syndrome cannot blatantly be given as a defense in all cases and yet should be considered by the judiciary. In the end, the paper puts forth the necessity of new law/legal provisions in making the judicial decisions objective and justiciable in case of battered women. DOI: https://doi.org/10.46985/jms.v6i2.203